1994
DOI: 10.1111/j.1464-410x.1994.tb07597.x
|View full text |Cite
|
Sign up to set email alerts
|

Alkali citrate prophylaxis in idiopathic recurrent calcium oxalate urolithiasis — a prospective randomized study

Abstract: An objective benefit of alkali citrate could not be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(55 citation statements)
references
References 18 publications
1
47
0
7
Order By: Relevance
“…Both sodium potassium citrate and potassium citrate alter urinary composition favourably [63][64][65][66][67][68][69], but the admixture of sodium might result in an increased calcium excretion or a less pronounce reduction in urinary calcium [37,70]. Clinical studies subsequently indicated that potassium citrate is superior to sodium potassium citrate in counteracting stone formation [71].…”
Section: Alkaline Citratementioning
confidence: 99%
“…Both sodium potassium citrate and potassium citrate alter urinary composition favourably [63][64][65][66][67][68][69], but the admixture of sodium might result in an increased calcium excretion or a less pronounce reduction in urinary calcium [37,70]. Clinical studies subsequently indicated that potassium citrate is superior to sodium potassium citrate in counteracting stone formation [71].…”
Section: Alkaline Citratementioning
confidence: 99%
“…Several authors supported the benefit of alkaline citrates in all patients undergoing shockwave lithotripsy for the significant improvement in rates of alleviation the calcium oxalate stone-forming activity and positively influence the preexisting stone clearance and dissolution with minor adverse reaction (2,11,(14)(15)(16). The studies with stone recurrence as the endpoint demonstrated a reduction in stone-forming rate from 47% to 100%.…”
Section: Discussionmentioning
confidence: 96%
“…The studies with stone recurrence as the endpoint demonstrated a reduction in stone-forming rate from 47% to 100%. Of four randomized controlled trials, the stone-free rate after at least two years of alkaline citrate treatment was 53.5% and 35% in treatment and placebo groups, respectively (3,(14)(15)(16). For three years, in idiopathic hypocitraturic calcium nephrolithiasis patients who received potassium citrate, the stone formation per year significantly declined from 1.20.6 to 0.1 ± 0.2 stones per patient.…”
Section: Discussionmentioning
confidence: 99%
“…9 Some positive trials of citrate did not require the intervention group to have hypocitruria. 10,11 In other words, citrate supplementation helps recurrent stone formers with normal range baseline urinary citrate. The same is true for several thiazide trials, which did not require hypercalciuria as an inclusion criterion.…”
Section: Drawbacksmentioning
confidence: 99%